Case Report: Disseminated Edwardsiella tarda infection in an immunocompromised patient - An, Lucia; Chan, June L.; Nguyen, Margaret; Yang, Shangxin; Deville, Jaime G. (Frontiers in Cellular and Infection Microbiology, 2023)
Human infection caused by bacteria of the Edwardsiella genus is rare and most often presents with gastroenteritis that rarely requires antibiotics. Our case report describes a medically complex patient with chronic steroid use contributing to an immunocompromised state, who presented with fever and abdominal pain. The patient was later found to have Edwardsiella tarda (E. tarda) bacteremia and underwent paracentesis confirming E. tarda bacterial peritonitis requiring a prolonged antibiotic course. This case report aims to illustrate the presentation, diagnosis, and management of an uncommon infection that can have severe complications especially among immunocompromised patients.